Wal-Mart wars moral populism in the twenty-first century - Massengill, Rebekah Peeples, 1975- (New York University Press, 2013)
Wal-Mart is America's largest retailer. The national chain of stores is a powerful stand-in of both the promise and perils of free market capitalism. Yet it is also often the target of public outcry for its labor practices, to say nothing of class-action lawsuits, and a central symbol in America's increasingly polarized political discourse over consumption, capitalism and government regulations. In many ways the battle over Wal-Mart is the battle between "Main Street" and "Wall Street" as the fate of workers under globalization and the ability of the private market to effectively distribute pr.